Suasana Toko, Kualitas Layanan, dan Kepuasan Pelanggan di Carrefour Cikarang - Sandra Amelia; Yayat Sujatna (Indonesian Journal of Economics Application (IJEA), 2020)
Every company always strives to succeed in winning the competition by trying to be able to achieve the goal of maintaining customers through satisfaction. Maintaining customer satisfaction is a challenge for companies that must be pursued for the survival of the company. The creation of a pleasant, attractive atmosphere, and can make consumers feel comfortable when in the shop and supported by excellent service quality is one way that customer satisfaction can be maintained. This research was conducted to analyze the influence of store atmosphere and service quality on customer satisfaction. This research was conducted using the associative descriptive method with an associative quantitative approach. Seventy, respondents, were sampled as respondents. The collected data were analyzed using multiple linear regression statistical tests, multiple correlations, and determination coefficients, while to determine whether or not the hypothesis was accepted the statistical test model F and t-test. Based on the results of multiple linear regression processing, we found that the atmosphere of the shop and the quality of service together- the same effect on consumer satisfaction. The percentage of the influence of these two variables on consumer satisfaction is 72.9%. The results of this study indicate that the store atmosphere and service quality partially affect customer satisfaction.